Time analysis of a judo fight - van Malderen, K.; van Herck Bram, R. K.; Zinzen, C. P. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Judo competition is characterised by an intermittent activity pattern. Knowledge of exact exercise and recuperation times in modern judo is necessary for an optimal preparation and fight simulation during the training period. Equally, changes in international regulations have drastically influenced the ne-waze (ground fight) time, the nage-waza (standing fight) time and the number of attacks during nage-waza fight. It was the aim of our study to determine the mean duration; the time spent in tachi-waza fight, the time spent in ne-waza fight, the number of attacks, the number of interruptions and the total interruption time during a judo fight. It was also hypothesised that patterns may vary in function of gender and in function of the weight categories. Methods All matches of the Belgian national championships (March 2003) were video taped and are under analysis. Analyses were performed per weight category for the different sexes. Preliminary results of the categories men -60kg and -66kg will be reported in this abstract. Results Three fights were analysed in the -60kg category and 4 in the -66 category. The total time of the fight was respectively 266 s for the -60kg category and 310 s for the -66kg category. Active time was respectively 183s and 222s with respectively 83s and 88s of interruption. The number of interruptions was 8 in the -60kg category and 11 in the -66kg category resulting in a mean interruption (recuperation) time of respectively 10s and 8s per interruption. Taking into account the total time on the judo floor and the number of interruptions brings us to activity intervals of respectively 30s and 28s. The mean nage-waza time was respectively 140s and 174s with 43s and 35s ne-waza time (respectively 23% and 21% ne waza time). During the nage-waza fight in the -60kg category there were 18 attacks (both players) meaning an action (attack or defending against the attack) every 7.7s. In the -66kg category we counted 35 attacks resulting in an action (attack or defending) every 5s. The mean duration of a ne-waza action was 14s in the -60kg category and 7.5 in the -66kg category. Discussion Our preliminary analysis indicates that in the lower weight categories (-60kg and -66kg) the nage-waza fight is predominant (respectively 77% and 79%) with only a minor part of the time spent in ne-waza. The mean interruption time of respectively 8 and 10 s may allow for some recuperation during the fight. Our results indicate that for the lowest weight categories most of the training should focus on nage-waza with the inclusion of 30s activity intervals interspersed with rest intervals of 10s. Due to the very short ne-waza actions, training should focus on efficiency of attacks and allow only some actions during a 10s training fight. Analysis of the higher weight categories and of the female categories may reveal other competition and hence training patterns.